Effect of graphene oxide and metallic fibers on the electromagnetic shielding effect of engineered cementitious composites. (July 2018) - Mazzoli, A.; Corinaldesi, V.; Donnini, J.; Di Perna, C.; Micheli, D.; Vricella, A.; Pastore, R.; Bastianelli, L.; Moglie, F.; Mariani Primiani, V.
Abstract: Electromagnetic shielding and propagation in concrete structures are getting more and more interest in radiation hazard problems and wireless communications. The protection of sensitive environment is nowadays carried out by appropriate shielding room made of metallic walls. Their efficacy is counteracted by their heaviness, not adequate for the installation over existing building walls. The using of concrete composites filled by conductive elements represents a valid alternative to metallic shielded room since they can be adopted to directly build up the building walls and/or to easily plaster existing walls. Graphene oxide powder and metallic fibers are being currently investigated as fillers in the manufacturing of electromagnetic shielding cementitious composites. The novelty of the present work is the characterization of a multi-reinforced cement realized by combining such two filler typologies: the synergistic effects of graphene oxide microparticles and short steel fibers result in enhancement of both mechanical properties and EMI effectiveness of the cementitious composites. Highlights: Electromagnetic shielding and propagation in concrete structures are getting interest. The protection of sensitive environment is nowadays carried out by appropriate shielding room made of metallic walls. The using of concrete composites filled by conductive elements represents a valid alternative to metallic shielded room. In the present paper graphene oxide powder and metallic fibers have been investigated as fillers in the manufacturing of electromagnetic shielding cementitious composites.